1996
DOI: 10.1210/jc.81.1.302
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by insulin of follicle-stimulating hormone and luteinizing hormone actions in human granulosa cells of normal and polycystic ovaries

Abstract: Anovulation in polycystic ovary syndrome (PCOS) is associated with hyperinsulinemia and insulin resistance, but it has been unclear whether the ovary is insulin resistant in women with PCOS. The aims of this study were, firstly, to determine whether human granulosa cells respond to physiological concentrations of insulin and, secondly, to investigate insulin and gonadotropin interactions in vitro in granulosa cells obtained from normal (N) and polycystic ovaries (PCO). Granulosa cells were incubated with insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
12

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(104 citation statements)
references
References 0 publications
3
89
0
12
Order By: Relevance
“…Anovulatory PCOS patients have a greater BMI than their ovulatory sisters despite a similar degree of ovarian hyperandrogenism [62], and weight loss in obese PCOS patients reverses anovulatory infertility [63]. Since insulin enhances FSHinduced upregulation of LH receptors in granulosa cells and increases their progesterone (P4) responsiveness to LH [64,65], hyperinsulinemia presumably induces premature follicle luteinization, which arrests cell proliferation and follicle growth. Consequently small antral PCOS follicles exhibit P4 hypersecretion and overexpress LH receptors [66,67], causing an exaggerated steroidogenic shift from E2 to P4 production [68].…”
Section: Impaired Follicle Growthmentioning
confidence: 99%
“…Anovulatory PCOS patients have a greater BMI than their ovulatory sisters despite a similar degree of ovarian hyperandrogenism [62], and weight loss in obese PCOS patients reverses anovulatory infertility [63]. Since insulin enhances FSHinduced upregulation of LH receptors in granulosa cells and increases their progesterone (P4) responsiveness to LH [64,65], hyperinsulinemia presumably induces premature follicle luteinization, which arrests cell proliferation and follicle growth. Consequently small antral PCOS follicles exhibit P4 hypersecretion and overexpress LH receptors [66,67], causing an exaggerated steroidogenic shift from E2 to P4 production [68].…”
Section: Impaired Follicle Growthmentioning
confidence: 99%
“…Insulin receptors are also expressed in granulosa cells, where they play a role in potentiating FSH-stimulated steroid secretion, as shown by increased estrogen secretion by granulosa cells exposed simultaneously to insulin and FSH [18]. In addition, the gonadotropic effect of insulin on folliculogenesis enhances the recruitment and growth of pre-ovulatory follicles [16], decreases the apoptosis and atresia of ovarian follicles [19], and stimulates the passage from primordial to primary follicles [20].…”
Section: Ovarian Function In T1d (Fig 1)mentioning
confidence: 99%
“…In women with T1DM, the aetiology of their hyperandrogenism is unclear, and it has been proposed that their hyperandrogenism is due to non-physiological insulin replacement therapy (4,5). Indeed, the results of several laboratory and clinical studies have found that insulin can also influence the production of ovarian and adrenal androgens (6,7,8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%